From Early Child Development to Human Development : Investing in Our Children's Future - Eming Young, Mary (Washington, DC: World Bank, 2013)
Investing in every child at an early age is an investment in human, and economic development for all. Children born in poverty are far more likely to grow undeveloped in both body, and mind. Science tells us that early child development (ECD) is critical, and marks a child for life, and, young children who are well nurtured, do better in school, and develop the skills to compete in a global economy. It is in this context that the Bank hosted a conference to review the state of knowledge on brain development, the link between ECD and human development, the standards of care to improve children's educational outcomes, the qualitative and quantitative measures of effective programs, and elements of quality in ECD programs. This book contains the proceedings of the Conference on Investing in our Children's Future, which brought together leading experts, academicians, and practitioners from nongovernmental organizations, civil society, governments, and international organizations. The conference featured the benefits of investing in young children, and measuring ECD standards of care, to ensure a fair start for all based on case studies. It further evaluated the effectiveness of ECD programs, with presentations focused on the role of private initiatives in influencing public policy. Conclusions include the pursuit of a continued evaluation on the effectiveness of ECD programs, and, a deliberately planned global coalition to fund ECD initiatives.